Pape Mashe Method in Developing Children's Creative Skills - Yaqubova Muhabbat Dilshodbekovna (International Journal on Integrated Education, 2022)
The accurate organization of activities in preschool education organizations using the pape-mache (crumpled paper) approach and their implementation are the topics of this essay, which is written for educators and students of preschool education organizations. We explain application and transfer.